Landasan Filsafat Ilmu Dalam Pengembangan Kurikulum Pendidikan Bahasa Arab - Riski Sirma Budi; M.Yunus Abu Bakar; Baiq Tuhfatul Unsi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study discusses the importance of the philosophical foundation of science in developing the Arabic language education curriculum to create holistic and critical learning. This approach is based on the view that language is not merely a communication tool, but also a means of thinking and shaping the intellectual character of students. This research is a library research using content analysis method on primary and secondary sources. The results show that the integration of the three pillars of the philosophy of science ontology, epistemology, and axiology in the Arabic language education curriculum produces comprehensive and balanced learning. Ontologically, Arabic is understood as a scientific entity with linguistic, religious, and cultural dimensions. Epistemologically, learning combines rationalism (logical reasoning) and progressivism (real experience). Axiologically, the curriculum is directed toward practical, moral, and spiritual values. Arabic language learning has proven potential to develop critical thinking skills through analyzing complex language structures, enriching cultural insights, and utilizing innovative technology. Thus, the philosophical foundation of science in the Arabic language education curriculum can produce learning that is not only oriented toward linguistic abilities, but also toward the formation of critical reasoning and wisdom values needed by students